PHILOSOPHY OF MATERIALITY - A MODEL FOR ITS DETERMINATION - Noles Monteblanco, Walter Adolfo (2016)
This research found a gap in the knowledge of accounting science, and especially in the auditing related specifically to the criteria for determining materiality. Thus, it is intended to contribute to the theoretical knowledge of accounting science; and especially to the auditing doctrine, strengthening the implementation of International Standards of Accounting and Financial Reporting (IAS / IFRS). The theoretical knowledge will result in technological procedures applicable to the financial auditing practice. It is unidentified whether auditing markets of the emerging economies have or lack, a clear criteria for that determination. We believe that the knowledge reported in this article- a summary of a research conducted by the author- is of great importance for these markets. Also, it will allow us to recognize the impact on auditing firms and independent auditors resulting on the benefit of the audited entities, representing more conceptual and theoretical knowledge about the auditing characteristics. By focusing the auditing under this perspective, we are expanding the scope and optimizing its tools to a higher level of organizations.